Anatomical study of the bud union in „Chip" and „T" budded 'Jonagold' apple trees on MM 106 rootstock - Végvári, Gy.; Hrotkó, K. (International Journal of Horticultural Science, 1999)
The traditional methods for vegetative propagation of apple and its varieties are the T-budding, and the winter grafting, but this latter way is a difficult and expensive procedure.In our experiment carried out in the Fruit Tree Nursery Soroksár, the healing process of chip- and T-budded apple trees 'Jonagold' on MM 106 rootstock was studied.The budding (T- and Chip-) was made in the first week of August, samples for microscope examination were taken monthly after this time until leaf fall.The investigated part of plants was made soft with 48 % HF (hydrogenfluoride), then cross and longitudinal section were made and examined by microscope.Based on analysis of microscope pictures in case of Chip-budding, it was established, that development had started quickly after budding on the rootstock and scion too. But the callus originated almost entirely from the rootstock tissue as new parenchyma cells fills the gap between the two components of graft (scion and stock), becoming interlocked and allowing for some passage of water and nutrients between the stock and the scion. This quantity of callus in case of T budding was under the scion buds larger, than the Chip-budded unions, where the thickness of callus mass is uniformly thick round the chip. The large mass of callus pushes the scion bud outwards from the shoot axis, which later results in a larger shoot-curvature above the bud union.Following this process on the Chip-budding it can be observed also, that a continuity of the cambium is established between bud and rootstock. Then the newly formed cambium started typical cambial activity, forming new xylem and phloem.Later the callus begins to lignify, and it is completed within about 3 months after budding.